Hobnail variant of papillary thyroid carcinoma showing goiter-like presentation and rapid growth. (27th January 2021) - Naciu, Anda Mihaela; Verri, Martina; Crescenzi, Anna; Taffon, Chiara; Longo, Filippo; Frasca, Luca; Tabacco, Gaia; Monte, Lavinia; Palermo, Andrea; Crucitti, Pierfilippo; Cesareo, Roberto
Abstract : Summary: We present the case of a 47-year-old Caucasian previously healthy woman with a voluminous thyroid nodule occupying almost the entire anterior neck region. The lesion had progressively increased in size during the previous 3 months and the patient presented intermittent symptoms of dysphagia and odynophagia with a slight change in voice. Fine needle aspiration showed papillary carcinoma. Based on imaging and cytological findings, the patient underwent total thyroidectomy. The surgical sample revealed a totally enlarged thyroid gland (weight: 208 g) with the presence of a poly-lobulated lesion centrally located and involving the isthmus and both lobes. Hobnail features were present in more than 30% of the neoplastic cells in agreement with the criteria for this subtype. Psammoma bodies and focal necrosis were also present. The extra-thyroidal extension included strap muscles and peri-esophageal glands. Immunohistochemistry using VE1 antibody for detecting BRAF-V600E mutation resulted positive. The final diagnosis was papillary thyroid carcinoma (PTC) hobnail variant (HVPTC)-pT4a. The HVPTC is a rare entity and, in most cases, appears like a unifocal lesion with a maximum tumor size of 8 cm reported so far. To our knowledge, this represents the largest tumor ever described (14 cm), showing rapid growth and with multinodular goiter-like aspect. Learning points: HVPTC is an aggressive variant of PTC, usually associated with radioactive iodine refractoriness, and a higher mortality rate compared to classic PTC. However, there is a marked individual variability in this association. HVPTC usually appears as small unifocal lesion but a multinodular goiter presentation may occur. The present case highlights that despite of the histology, our patient achieved a high ablation success rate after radioactive iodine therapy.